Study on Fintech Adoption: Examining the Customer Innovativeness and Attitude Towards the Adoption of Fintech Services - Jisha TP (PT FORMOSA CENDEKIA GLOBAL, 2024)
Technology plays an important role in the area of finance and now it become common among people. but whatever the technological advancement in the field of finance, many people are there who don’t have access to formal financial institutions and many researchers found that this can be solved with the help of technology adoption. Here the study focused on the Fintech adoption among the people with the help of the variables Fintech adoption, perceived ease of use, perceived usefulness, user innovation and the attitude towards the financial technology. the researcher utilized both primary and secondary data. Then the samples were selected from Pattambi taluk of Palakkad district-Kerala, based on convenience sampling method and distributed the questionnaire among 300 respondents. then 250 samples were selected from 300 by considering the data accuracy. Then the researcher utilized descriptive statistics and t-test, correlation coefficient, and regression analysis to conclude then the factor analysis was also utilized to understand the relation between the observed variable and the latent constructs. The study discovered that perceived usefulness and perceived ease of use have a stronger correlation with Fintech adoption. then there is a positive correlation between the customer's perceived usefulness of Fintech adoption and their attitude towards it. To increase customer satisfaction, Fintech companies can develop their services based on the perceived usefulness, ease of use, and attitude of customers in particular segments